Heterologia e alteridade social ou a comunicação pela margem - Joron, Philippe (2009)
This article proposes to highlight Georges Bataille’s notion of heterology, including it among the heuristic paradigms of the sociology of culture and communications studies. Conceived originally as the science of what is strange to the mainstream, this transgressive approach to social bonds may help open up the full range of meanings usually given to otherness and to exchange.